2014
DOI: 10.1089/rej.2013.1450
|View full text |Cite
|
Sign up to set email alerts
|

Calorie Restriction Down-Regulates Expression of the Iron Regulatory Hormone Hepcidin in Normal and d-Galactose–Induced Aging Mouse Brain

Abstract: It has been shown that iron progressively accumulates in the brain with age. Calorie restriction (CR) may allay many of the adverse effects of aging on the brain, yet the underlying mechanisms, in particular in relation to brain iron metabolism, remain unclear. This study aimed to investigate the role of CR in the regulation of cerebral cellular iron homeostasis. C57BL/6 mice were randomly divided into four groups of eight. The control group was fed a conventional diet ad libitum; the CR group received 70% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Our results show mRNA induction at 4 and 24 h in both the ispsilateral and contralateral sides of the brain, which implicates a specific pathway for iron homeostasis in the brain. This is consistent with recent studies showing induction of hepcidin mRNA in the brain in a D-galactose model of aging (Wei et al, 2014) in cultured astrocytes and microglia, but not in neurons (Urrutia et al, 2013), as well as a consequence of ischemia in an MCA occlusion model (Ding et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Our results show mRNA induction at 4 and 24 h in both the ispsilateral and contralateral sides of the brain, which implicates a specific pathway for iron homeostasis in the brain. This is consistent with recent studies showing induction of hepcidin mRNA in the brain in a D-galactose model of aging (Wei et al, 2014) in cultured astrocytes and microglia, but not in neurons (Urrutia et al, 2013), as well as a consequence of ischemia in an MCA occlusion model (Ding et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Local hepcidin expression in the brain has been an object of investigation of different studies. In physiological conditions hepcidin expression in brain structures and cells (neurons, glial cells, endothelial cells, epithelial cells of choroid plexus) has been consistently observed by in vivo studies in humans and rodents, albeit in low levels ( Krause et al, 2000 ; Pigeon et al, 2001 ; Zechel et al, 2006 ; Wang et al, 2008 , 2010 ; Hänninen et al, 2009 ; Raha et al, 2013 ; Wei et al, 2014 ; Farajdokht et al, 2015 ; Raha-Chowdhury et al, 2015 ; Graf et al, 2016 ; Li Y. et al, 2016 ; Pan et al, 2016 ; Tan et al, 2016 ; Lu et al, 2017 ; You et al, 2017 ; Zhang et al, 2017 ). Data from human and animal studies suggest that local hepcidin is more robustly expressed in pathophysiological states ( Sun et al, 2012 ; Urrutia et al, 2013 ; Tan et al, 2016 ; Xiong et al, 2016 ; You et al, 2017 ; Zhang et al, 2017 ).…”
Section: Brain Hepcidin Expression and Mechanisms Of Regulationmentioning
confidence: 83%
“…In vivo experiments during brain inflammation show that the use of iron chelation protects from brain iron overload, reduces microglial activation and improves cognitive functions in rodents by reducing levels of hepcidin and increasing levels of FPN in hippocampus ( Li Y. et al, 2016 ; Pan et al, 2016 ). In addition, maternal diet and calorie restriction have been proposed as factors that offer neuroprotection by reducing brain iron load through suppression of brain hepcidin ( Wei et al, 2014 ; Graf et al, 2016 ). But, it is interesting to notice that accumulating data suggest that hepcidin role in neuronal iron load and inflammation is ambiguous; hepcidin can protect from iron load, but also can cause iron load during inflammation.…”
Section: Dual Role Of Hepcidin In Brain Pathologies; Implications Formentioning
confidence: 99%
“…Previous studies have reported lowering effect of metformin on iron stores after 12 weeks of treatment in women with polycystic ovary syndrome, a condition associated with insulin resistance . Studies in animals have shown higher iron requirements in diet‐induced obese rats , and down‐regulation of hepcidin expression in brains of mice under calorie restriction .…”
Section: Introductionmentioning
confidence: 99%